Evaluation Of Risk Management Maturity Of A Fintech Firm In Indonesia - Franciskus Antonius Alijoyo; Ivonne Bonita; Kevin Bastian Sirait (Eduvest - Journal of Universal Studies, 2021)
This study identified the risk management maturity status, revealed the major sources of the firm risk management maturity, issues in running quality risk management of a financial technology firm in Indonesia, and recommended enhancements. It used the Risk and Insurance Management Society – Risk Maturity Model to evaluate the risk management maturity status. To get detailed information about the risk management implementation, the researchers also did observations and interviews. This study confirmed that the firm was in ad-hoc status. The firm was overconfident of their previous success in implementing risk management and careless in transforming the risk management concepts into real practices. Thus, they lost their ability to decide appropriate decisions in handling the risks that they faced. As a result, they could not run effective and efficient management. Detail findings and recommendations on the risk management maturity of the firm are provided in this article.